Delayed heamatoma after melanoma metastasis resection upon restart of Immunotherapy: Case Report and Review of the Literature. (12th October 2019) - Elhag, Ali; Lavrador, José; Frantzias, Joseph; Kailaya-Vasan, Ahilan; Gullan, Richard; Ghimire, Prajwal; Vergani, Francesco; Ashkan, Keyoumars; Bhangoo, Ranjeev
Abstract: Background: Supratentorial Metastatic Melanomas are common and increasingly treated with immunotherapy. While improving the outcome, the immunotherapy potentially increases the risks of the intracranial surgical procedures, particularly bleeding. However, scarce reports address this complications. Case Description: A 52-year old male with a history of right upper limb excised skin lesion resected with wide local excision 6 months prior to admission, who presented with a three weeks history of progressive headaches, vomiting, odd behaviours, forgetfulness, and left lower sided weakness. Brain imaging showed a right frontal lesion with evidence of haemorrhage within it with midline shift and mass effect. He underwent craniotomy and resection of the lesion with no post-operative complication, resolution of left sided hemiparesis and post-operative imaging documenting complete resection and no post-operative complications. The histopathology confirmed metastatic melanoma and he received adjuvant immunotherapy (Nivolumab), however he represented 4 weeks post operatively with sudden onset headache with vomiting with no neurological deficit, brain imaging showed a delayed hematoma in the surgical site. Conclusions: This case report highlights the risk of post-operative bleeding with the immunotherapy and paves the way for further studies with regards to the safety of immunotherapy after intracranial procedures